2014
DOI: 10.2337/db13-0665
|View full text |Cite
|
Sign up to set email alerts
|

HSP72 Is a Mitochondrial Stress Sensor Critical for Parkin Action, Oxidative Metabolism, and Insulin Sensitivity in Skeletal Muscle

Abstract: Increased heat shock protein (HSP) 72 expression in skeletal muscle prevents obesity and glucose intolerance in mice, although the underlying mechanisms of this observation are largely unresolved. Herein we show that HSP72 is a critical regulator of stress-induced mitochondrial triage signaling since Parkin, an E3 ubiquitin ligase known to regulate mitophagy, was unable to ubiquitinate and control its own protein expression or that of its central target mitofusin (Mfn) in the absence of HSP72. In wild-type cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
109
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(122 citation statements)
references
References 57 publications
10
109
2
1
Order By: Relevance
“…Body composition analysis revealed an increase in body weight, fat mass, and body fat percentage (Fig. 5a-d) with high-fat feeding, but in line with previous analysis of these mice at 20 weeks of age (Drew et al 2014), no difference in weight was detected with the deletion of Hsp72. Consistent with what was observed with the Hsp72 Tg mice, no difference in heart mass was detected ( Fig.…”
Section: Hsp72supporting
confidence: 68%
See 3 more Smart Citations
“…Body composition analysis revealed an increase in body weight, fat mass, and body fat percentage (Fig. 5a-d) with high-fat feeding, but in line with previous analysis of these mice at 20 weeks of age (Drew et al 2014), no difference in weight was detected with the deletion of Hsp72. Consistent with what was observed with the Hsp72 Tg mice, no difference in heart mass was detected ( Fig.…”
Section: Hsp72supporting
confidence: 68%
“…Despite the documented alterations in metabolic processes in the skeletal muscle of Hsp72 gain of function (Hsp72 Tg) or Hsp72 loss of function models (Hsp72 KO) (Chung et al 2008;Drew et al 2014;Henstridge et al 2014), our study finds little evidence that these changes also occur in cardiac tissue. This suggests that Hsp72 may play an organ-specific role in modulating metabolic processes.…”
Section: Discussioncontrasting
confidence: 39%
See 2 more Smart Citations
“…HSP60, mtHSP70, and TNF receptor-associated protein 1 [TRAP-1]) were dramatically increased by heat stress treatment 20,43,48) . Furthermore, an interesting observation was recently reported that HSP72, conventionally considered as cytosolic HSP, translocates to mitochnodria from cytosol and interacts with Parkin in response to increased mitochondrial stress 50) . Therefore, in addition to an assay of protein, analyzing properties of HSPs at the post-translational level (e.g.…”
Section: Conflicts Of Interestsmentioning
confidence: 99%